Expanded graphite and preparation method thereof, and composite phase change material and preparation method thereof

By oxidation interpolation, auxiliary interpolation and expansion treatment of expanded graphite, the existing problem of small expansion volume of expanded graphite is solved, and higher expansion volume and better heat transfer performance are achieved.

CN119503790AActive Publication Date: 2025-02-25JILIN UNIVERSITY

Patent Information

Application Number
CN202411707856.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing expanded graphite has a small expansion volume, which limits its application in phase change materials, especially in improving heat transfer properties.

Method used

Expanded graphite is prepared by mixing hydrogen peroxide, concentrated sulfuric acid and flake graphite for oxidation, then mixing with auxiliary intercalation agent for auxiliary intercalation, and finally undergoing expansion treatment, and expanding graphite has a significant increase in expansion volume.

Benefits of technology

The prepared expanded graphite has a higher expansion volume, which can further improve heat transfer performance, and while increasing the thermal conductivity, it loses less latent heat of phase change.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154958700000031
    Figure BDA0005154958700000031
  • Figure BDA0005154958700000041
    Figure BDA0005154958700000041
  • Figure BDA0005154958700000081
    Figure BDA0005154958700000081
Patent Text Reader

Abstract

The invention belongs to the technical field of phase change materials, and particularly relates to expanded graphite and a preparation method thereof, and a composite phase change material and a preparation method thereof. The expanded graphite obtained by the preparation method provided by the invention has a relatively high expansion volume, can further improve the heat transfer performance when being applied to the phase change material, and can reduce the phase change latent heat loss while improving the heat conductivity coefficient. Furthermore, the invention provides a composite phase change material. The beef tallow, the high-melting-point paraffin and the expanded graphite are directly and simply mixed, and the utilization rate of biomass resources can be increased by controlling different proportions of the beef tallow, the high-melting-point paraffin and the expanded graphite; the phase change latent heat of the phase change material can be improved while the melting point is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phase change materials, and in particular relates to expanded graphite and a preparation method thereof, a composite phase change material and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles, power batteries, as one of the core components, have become the focus of research and attention. The range and safety of power batteries have also become the main issues restricting the development of new energy vehicles. At present, lithium-ion power batteries are widely used in electric vehicles. Compared with other rechargeable batteries, lithium-ion batteries have the advantages of high energy density, low self-discharge rate, low maintenance requirements, long cycle life, light weight, and high compactness. However, the operating performance of lithium-ion batteries is greatly affected by the ambient temperature, and the battery can only be operated safely and efficiently within a relatively narrow temperature range. At low temperatures, the internal resistance of lithium-ion batteries will increase rapidly, the charge and discharge capacity will be significantly reduced, and the number of charge and discharge cycles will be greatly reduced. High-speed charging and discharging of batteries at too low temperatures will also cause safety problems such as internal short circuits. In a high-temperature environment, if the battery temperature is not effectively controlled, the high temperature will cause the internal SEI film and the positive and negative active materials to decompose in turn, and the diaphragm will melt, resulting in an internal chain chemical reaction and generating a large amount of heat, leading to safety accidents such as battery thermal runaway.

[0003] In order to ensure the working performance and thermal safety of lithium-ion batteries, the batteries must be maintained in an appropriate temperature range. However, due to the large temperature difference between the north and the south in winter, the cold climate in the north may cause the battery to degrade in performance and shorten its service life during high-speed charging and discharging, and even cause safety problems such as thermal runaway. Phase change material (PCM) cooling technology is able to maintain the operating temperature of the battery within a relatively constant temperature range, absorbing / releasing a large amount of heat during the phase change process. This solution can keep the temperature within the optimal range and manage uniform temperature distribution, especially in extreme environments. With the deepening of research on phase change materials, PCM has attracted widespread attention due to its simple structure, strong shape adaptability, and no additional energy consumption.

[0004] Expanded graphite (EG) is a commonly used material. Compared with metals, it has many advantages, such as rich pores, low chemical activity, strong adsorption and low density. Most importantly, it has high thermal conductivity. It is widely used to enhance the thermal performance of phase change materials. However, the expansion volume of existing expanded graphite is small, which limits the application of expanded graphite in phase change materials. Summary of the invention

[0005] The object of the present invention is to provide an expanded graphite and a preparation method thereof, a composite phase change material and a preparation method thereof. The expanded graphite prepared by the preparation method provided by the present invention has a higher expansion volume and is applied to phase change materials to further improve heat transfer performance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing expanded graphite, comprising the following steps:

[0008] Mixing hydrogen peroxide, concentrated sulfuric acid and flake graphite to perform oxidation intercalation to obtain intercalated graphite;

[0009] The intercalated graphite and an auxiliary intercalation agent are mixed to perform auxiliary intercalation to obtain expandable graphite; the auxiliary intercalation agent includes copper nitrate, ammonium nitrate or zinc nitrate;

[0010] The expandable graphite is expanded to obtain expanded graphite.

[0011] Preferably, the mass concentration of the hydrogen peroxide is 30%; the mass concentration of the concentrated sulfuric acid is 98%;

[0012] The volume ratio of hydrogen peroxide to concentrated sulfuric acid is 0.25:5.5-7;

[0013] The usage ratio of the concentrated sulfuric acid and flake graphite is 5.5-7 mL: 2 g.

[0014] Preferably, the temperature of the oxidation intercalation is 35-45° C. and the time is 25-45 min.

[0015] Preferably, the mass ratio of the flake graphite to the auxiliary intercalant is 2:0.24-0.3;

[0016] The temperature of the auxiliary intercalation is 35-45° C., and the time is 25-45 minutes.

[0017] Preferably, the expansion temperature is 900-1000°C.

[0018] The present invention also provides expanded graphite prepared by the preparation method described in the above technical solution.

[0019] The present invention also provides a composite phase change material, including paraffin, tallow and expanded graphite;

[0020] The expanded graphite is the expanded graphite described in the above technical solution.

[0021] Preferably, the melting point of the paraffin wax is 100-107°C;

[0022] The mass ratio of the paraffin wax to the tallow is 1-9:1-9; the mass percentage of the expanded graphite in the composite phase change material is 4.5-5.5%.

[0023] Preferably, the melting point of the composite phase change material is 70-80° C., and the latent heat of phase change is 54.55-202.8 J / g.

[0024] The present invention also provides a method for preparing the composite phase change material described in the above technical solution, comprising the following steps: mixing paraffin wax, tallow and expanded graphite to obtain the composite phase change material.

[0025] The present invention provides a method for preparing expanded graphite, comprising the following steps: mixing hydrogen peroxide, concentrated sulfuric acid and flake graphite, performing oxidation intercalation, and obtaining intercalated graphite; mixing the intercalated graphite and an auxiliary intercalation agent, performing auxiliary intercalation, and obtaining expandable graphite; the auxiliary intercalation agent comprises copper nitrate, ammonium nitrate or zinc nitrate; and expanding the expandable graphite to obtain expanded graphite. The expanded graphite obtained by the preparation method provided by the present invention has a high expansion volume, and is applied to phase change materials, which can further improve the heat transfer performance, and can lose less phase change latent heat while improving the thermal conductivity.

[0026] The present invention also provides a composite phase change material, including paraffin, tallow and expanded graphite; the expanded graphite is the expanded graphite described in the above technical solution. In the present invention, the raw material source of tallow is wide and the production cost is low. Compared with synthetic materials that require complex chemical synthesis, the economic advantage of tallow is significant. At the same time, compared with synthetic phase change materials such as organic waxes or polymers, it has a relatively high melting point (usually between 30 and 40°C). In addition, the good heat storage capacity and low thermal conductivity of tallow make it competitive in thermal management. At the same time, as a bio-based material, tallow has little impact on the environment, which meets the current demand for sustainable materials. The present invention directly performs a simple mixing process on tallow, high melting point paraffin and expanded graphite, and by controlling the different proportions of the three, it is beneficial to improve the utilization rate of biomass resources; it can significantly reduce the melting point while increasing the phase change latent heat of the phase change material. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing expanded graphite, comprising the following steps:

[0028] Mixing hydrogen peroxide, concentrated sulfuric acid and flake graphite to perform oxidation intercalation to obtain intercalated graphite;

[0029] The intercalated graphite and an auxiliary intercalation agent are mixed to perform auxiliary intercalation to obtain expandable graphite; the auxiliary intercalation agent includes copper nitrate, ammonium nitrate or zinc nitrate;

[0030] The expandable graphite is expanded to obtain expanded graphite.

[0031] The invention mixes hydrogen peroxide, concentrated sulfuric acid and flake graphite, performs oxidation intercalation, and obtains intercalated graphite.

[0032] In the present invention, the mass concentration of the hydrogen peroxide is preferably 30%; the mass concentration of the concentrated sulfuric acid is preferably 98%; the volume ratio of the hydrogen peroxide to the concentrated sulfuric acid is preferably 0.25:5.5-7, specifically 0.25:5.5, 0.25:6, 0.25:6.5 or 0.25:7; the amount ratio of the concentrated sulfuric acid to the flake graphite is preferably 5.5-7mL:2g, specifically 5.5mL:2g, 6mL:2g or 7mL:2g.

[0033] In the present invention, the mixing process preferably includes: mixing hydrogen peroxide and concentrated sulfuric acid evenly, and then adding flake graphite. In the present invention, the temperature of the oxidation intercalation is preferably 35-45°C, specifically 30°C, 35°C or 40°C; the time is preferably 25-45min, specifically 25min, 30min, 35min, 40min or 45min. In the present invention, the oxidation intercalation is preferably carried out under stirring, and the stirring speed is preferably 200rpm. After the oxidation intercalation, it is preferred not to carry out any subsequent treatment, and the subsequent auxiliary intercalation is directly carried out.

[0034] In the present invention, the oxidation intercalation process includes an oxidation reaction and an intercalation reaction. The equation of the oxidation reaction is shown in Formula 1, and the equation of the intercalation reaction is shown in Formula 2:

[0035]

[0036] After obtaining the intercalated graphite, the present invention mixes the intercalated graphite with an auxiliary intercalation agent to perform auxiliary intercalation to obtain expandable graphite; the auxiliary intercalation agent includes copper nitrate, ammonium nitrate or zinc nitrate.

[0037] In the present invention, the auxiliary intercalation agent includes copper nitrate, ammonium nitrate or zinc nitrate, preferably ammonium nitrate. In the present invention, the mass ratio of the flake graphite to the auxiliary intercalation agent is preferably 2:0.24-0.3, specifically 2:0.24, 2:0.27 or 2:0.30; the temperature of the auxiliary intercalation is preferably 35-45°C, specifically 30°C, 35°C or 40°C; the time is preferably 25-45min, specifically 25min, 30min, 35min, 40min or 45min. In the present invention, the auxiliary intercalation is preferably carried out under stirring, and the stirring speed is preferably 200rpm.

[0038] In the present invention, the reaction equation in the auxiliary intercalation process is shown in Formula 3;

[0039]

[0040] In the present invention, the auxiliary intercalation agent is used on the basis of preparing low-sulfur expandable graphite by sulfuric acid-nitric acid mixing method, and according to the reaction of nitrate and concentrated sulfuric acid to generate nitric acid and hydrogen sulfate, they are reacted in concentrated sulfuric acid to generate nitric acid. Under the joint action of nitric acid, sulfuric acid and nitrate, the natural flake graphite is subjected to oxidation intercalation reaction, so that the flake graphite has a moderate oxidation degree and a sufficient amount of interlayer inserts, and the expandable graphite with better quality is obtained.

[0041] In the present invention, the temperature of the oxidation intercalation layer is preferably the same as the temperature of the auxiliary intercalation layer; and the time of the oxidation intercalation layer is preferably the same as the time of the auxiliary intercalation layer.

[0042] After the auxiliary intercalation, the present invention also preferably includes filtering the obtained system, washing the obtained precipitate with water until it is neutral, and then drying; the drying temperature is preferably 60-90°C, specifically 60°C, 70°C, 80°C or 90°C; and the drying time is preferably 4h.

[0043] After obtaining the expandable graphite, the present invention expands the expandable graphite to obtain expanded graphite.

[0044] In the present invention, the expansion temperature is preferably 900-1000°C.

[0045] The present invention also provides expanded graphite prepared by the preparation method described in the above technical solution. In the present invention, the collision volume of the expanded graphite is preferably 310 to 380 mL / g.

[0046] The present invention also provides a composite phase change material, including paraffin, tallow and expanded graphite;

[0047] The expanded graphite is the expanded graphite described in the above technical solution.

[0048] In the present invention, the melting point of the paraffin wax is preferably 100-107°C, specifically 100°C, 103°C, 105°C or 107°C. In the present invention, the mass ratio of the paraffin wax to tallow is preferably 1-9:1-9, specifically 1:1, 3:7, 7:3, 1:9 or 9:1. In the present invention, the mass percentage of the expanded graphite in the composite phase change material is preferably 4.5-5.5%, specifically 4.5%, 5.0% or 5.5%.

[0049] In the present invention, the melting point of the composite phase change material is preferably 70-80° C., and the phase change latent heat is preferably 54.55-202.8 J / g.

[0050] The present invention also provides a method for preparing the composite phase change material described in the above technical solution, comprising the following steps:

[0051] The composite phase change material is obtained by mixing paraffin wax, beef tallow and expanded graphite.

[0052] In the present invention, the mixing process preferably includes:

[0053] Heat and melt paraffin and tallow, and condense to obtain a solid mixture;

[0054] The solid mixture and expanded graphite are stirred and mixed.

[0055] In the present invention, the temperature of the heating and melting is preferably 120° C. In the present invention, the rotation speed of the stirring and mixing is preferably 200 to 400 rpm, and the time is preferably 1 to 3 hours.

[0056] After the mixing, the present invention also preferably includes solidifying and compacting the obtained mixed system at room temperature.

[0057] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0058] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] Example 1

[0060] 0.25 mL of oxidizing agent hydrogen peroxide with a mass concentration of 30% and 5.5 mL of concentrated sulfuric acid with a mass concentration of 98% are uniformly mixed, and 2 g of flake graphite is added to the mixture for oxidation intercalation reaction, and the reaction is carried out at a water bath temperature of 40° C. for 30 minutes (accompanied by stirring at a speed of 200 rpm); 0.24 g of auxiliary intercalating agent ammonium nitrate is added to the mixed system for auxiliary intercalation agent, and the reaction is carried out at a water bath temperature of 40° C. for 30 minutes (accompanied by stirring at a speed of 200 rpm), and then filtered and washed with water to neutrality; the above product is dried at 80° C. for 4 hours to obtain expandable graphite; the expandable graphite is expanded at 900° C. to obtain expanded graphite.

[0061] Example 2

[0062] Expanded graphite was prepared in the same manner as in Example 1, wherein the amount of ammonium nitrate added was 0.27 g.

[0063] Example 3

[0064] Expanded graphite was prepared in the same manner as in Example 1, wherein the amount of ammonium nitrate added was 0.30 g.

[0065] Example 4

[0066] Expanded graphite was prepared in the manner of Example 2, wherein the oxidation intercalation time was 25 min and the auxiliary intercalation time was 25 min.

[0067] Example 5

[0068] Expanded graphite was prepared in the manner of Example 2, wherein the oxidation intercalation time was 35 min and the auxiliary intercalation time was 35 min.

[0069] Example 6

[0070] Expanded graphite was prepared in the manner of Example 2, wherein the oxidation intercalation time was 40 min and the auxiliary intercalation time was 40 min.

[0071] Example 7

[0072] Expanded graphite was prepared in the manner of Example 2, wherein the oxidation intercalation time was 45 min and the auxiliary intercalation time was 45 min.

[0073] Example 8

[0074] Expanded graphite was prepared in the manner of Example 2, wherein the amount of concentrated sulfuric acid used was 6 mL.

[0075] Example 9

[0076] Expanded graphite was prepared in the manner of Example 2, wherein the amount of concentrated sulfuric acid used was 6.5 mL.

[0077] Example 10

[0078] Expanded graphite was prepared in the manner of Example 2, wherein the amount of concentrated sulfuric acid was 7 mL.

[0079] Embodiment 11

[0080] Expanded graphite was prepared in the same manner as in Example 2, wherein the drying temperature was 60°C.

[0081] Example 12

[0082] Expanded graphite was prepared in the same manner as in Example 2, wherein the drying temperature was 70°C.

[0083] Comparative Example 1

[0084] Expanded graphite was prepared in the same manner as in Example 2, wherein the amount of ammonium nitrate added was 0.21 g

[0085] Comparative Example 2

[0086] Expanded graphite was prepared in the manner of Example 2, wherein the amount of concentrated sulfuric acid used was 4.5 mL.

[0087] Comparative Example 3

[0088] Expanded graphite was prepared in the manner of Example 2, wherein the amount of concentrated sulfuric acid used was 5 mL.

[0089] Comparative Example 4

[0090] Expanded graphite was prepared in the manner of Example 2, wherein the temperature of the oxidation intercalation layer and the temperature of the auxiliary intercalation layer were 30°C.

[0091] Comparative Example 5

[0092] Expanded graphite was prepared in the manner of Example 2, wherein the temperature of the oxidation intercalation layer and the temperature of the auxiliary intercalation layer were 50°C.

[0093] Comparative Example 6

[0094] Expanded graphite was prepared in the same manner as in Example 2, wherein the drying temperature was 50°C.

[0095] Comparative Example 7

[0096] Expanded graphite was prepared in the same manner as in Example 2, wherein the drying temperature was 90°C.

[0097] Comparative Example 8

[0098] Commercially available expanded graphite was used as a comparative example.

[0099] Test Example 1

[0100] The expansion volume of the expanded graphite obtained in Examples 1 to 12 and Comparative Examples 1 to 8 was tested according to the national standard GB 10698-1989, and the results are shown in Table 1.

[0101] Table 1 Expansion volume of expanded graphite of Examples and Comparative Examples

[0102] Example 1 Example 2 Example 3 Example 4 Example 5 Expansion volume (mL / g) 330 380 310 330 350 Example 6 Example 7 Example 8 Example 9 Example 1 Swelling volume (mL / g) 350 350 330 330 330 Embodiment 11 Example 12 Comparative Example 1 Comparative Example 2 Comparative Example 3 Swelling volume (mL / g) 350 380 290 260 300 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Swelling volume (mL / g) 300 300 300 260 300

[0103] It can be seen from Table 1 that the preparation conditions of expanded graphite are closely related to its expansion volume. By comparison, it can be shown that the expansion volume of the expanded graphite prepared by the present invention is greater than that of conventional expanded graphite on the market.

[0104] Embodiment 13

[0105] 1 g of butter and 9 g of high melting point paraffin (melting point 105° C.) were heated and melted, and the two were mixed and heated at a constant temperature and stirred to obtain a mixed system, and the system temperature was controlled at 120° C. during the mixing process; the mixed system was condensed at room temperature to obtain a solid mixture;

[0106] The solid mixture and the expanded graphite prepared in Example 2 were stirred and mixed at a rotation speed of 200 rpm for 2 hours, and the obtained mixture was solidified and compacted at room temperature to obtain a composite phase change material, wherein the mass percentage of the expanded graphite in the composite phase change material was 5%.

[0107] Embodiment 14

[0108] A composite phase change material was prepared in the manner of Example 13, wherein 3 g of tallow and 7 g of high melting point paraffin were added.

[0109] Embodiment 15

[0110] A composite phase change material was prepared in the manner of Example 13, wherein 5 g of tallow and 5 g of high melting point paraffin were added.

[0111] Example 16

[0112] A composite phase change material was prepared in the manner of Example 13, wherein 7 g of tallow and 3 g of high melting point paraffin were added.

[0113] Embodiment 17

[0114] A composite phase change material was prepared in the manner of Example 13, wherein 9 g of tallow and 1 g of high melting point paraffin were added.

[0115] Embodiment 18

[0116] A composite phase change material was prepared in the manner of Example 13, wherein the solid mixture and the expanded graphite were mixed for 1 hour.

[0117] Embodiment 19

[0118] A composite phase change material was prepared in the manner of Example 13, wherein the solid mixture and the expanded graphite were mixed for 3 hours.

[0119] Comparative Example 9

[0120] A commercially available high melting point paraffin material was used as a comparative example.

[0121] Comparative Example 10

[0122] Commercially available butter material was used as a comparative example.

[0123] Comparative Example 11

[0124] A commercially available paraffin-based phase change material is used as a comparative example.

[0125] Test Example 2

[0126] The melting points of the composite phase change materials of Examples 13 to 17 and the products of Comparative Examples 9 to 10 were tested by a melting point instrument, and the phase change latent heat of the composite phase change materials of Examples 13 to 17 and the products of Comparative Examples 9 to 10 were tested by a differential scanning calorimeter. The test results are shown in Table 2.

[0127] Table 2 Performance parameters of phase change materials of embodiments and comparative examples

[0128]

[0129]

[0130] It can be seen from Table 2 that adding a small amount of tallow to high-melting-point paraffin with a melting point of 107°C can reduce the melting point, and the phase change latent heat loss is small. The phase change latent heat is much higher than the phase change latent heat of the tallow itself, indicating that the paraffin / tallow-based phase change material provided by the present invention has good heat storage performance and low cost.

[0131] Test Example 2

[0132] The thermal stability of the products of Examples 13, 18 to 19 and Comparative Example 11 as phase change materials was tested according to the following method; 10 g of the phase change material was pressed into shape at the same pressure, placed in an oven and heated at a constant temperature of 90° C. for 1 hour, the mass of the phase change material before and after heating was weighed and its weight loss rate was calculated. The results are listed in Table 3.

[0133] Table 3 Weight loss rate of the products of the embodiments and comparative examples

[0134] Example Before heating(g) After heating(g) Weight loss rate (%) Example 13 9.645 9.638 0.07 Embodiment 18 9.704 9.670 0.35 Embodiment 19 9.690 9.680 0.10 Comparative Example 11 9.776 9.741 0.36

[0135] To further test the thermal stability of the products of Examples 13, 18 to 19 and Comparative Example 11 as phase change materials, 10 g of the phase change material was pressed into shape at the same pressure, placed in an oven and heated at a constant temperature of 90°C for 1 hour, cooled along with the furnace, the mass of the sample was weighed, the heating and cooling cycle was repeated 30 times, the mass change was recorded and the weight loss rate was calculated. The results are listed in Table 4.

[0136] Table 4 Weight loss rate of the products of the embodiments and comparative examples

[0137] Example Before cycle (g) After cycle (g) Weight loss rate (%) Example 13 9.638 9.565 0.76 Embodiment 18 9.670 9.581 0.92 Embodiment 19 9.680 9.595 0.88 Comparative Example 11 9.741 9.650 0.93

[0138] It can be seen from Tables 3 and 4 that the infiltration time of the paraffin / tallow-based phase change material directly affects the thermal stability of the phase change material. Only the paraffin / tallow-based phase change material prepared under the optimal reaction conditions can have the best stability. At the same time, through the comparative examples, we can see that the paraffin / tallow-based phase change material prepared in the present invention has higher stability than the conventional phase change materials on the market.

[0139] In summary, it can be seen that the method provided by the present invention has a high utilization rate for tallow and flake graphite, and the prepared paraffin / tallow-based phase change material has excellent heat storage performance.

[0140] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing expanded graphite, characterized in that: The following steps are involved: Mixing hydrogen peroxide, concentrated sulfuric acid and flake graphite to perform oxidation intercalation to obtain intercalated graphite; The intercalated graphite and an auxiliary intercalation agent are mixed to perform auxiliary intercalation to obtain expandable graphite; the auxiliary intercalation agent includes copper nitrate, ammonium nitrate or zinc nitrate; The expandable graphite is expanded to obtain expanded graphite.

2. The preparation method according to claim 1, characterized in that: The mass concentration of the hydrogen peroxide is 30%; the mass concentration of the concentrated sulfuric acid is 98%; The volume ratio of hydrogen peroxide to concentrated sulfuric acid is 0.25:5.5-7; The usage ratio of the concentrated sulfuric acid and flake graphite is 5.5-7 mL: 2 g.

3. The preparation method according to claim 1, characterized in that: The temperature of the oxidation intercalation is 35-45° C. and the time is 25-45 minutes.

4. The preparation method according to claim 2, characterized in that: The mass ratio of the flake graphite to the auxiliary intercalant is 2:0.24-0.3; The temperature of the auxiliary intercalation is 35-45° C., and the time is 25-45 minutes.

5. The preparation method according to claim 1, characterized in that: The expansion temperature is 900-1000°C.

6. Expanded graphite prepared by the preparation method according to any one of claims 1 to 5.

7. A composite phase change material, characterized in that: Includes paraffin wax, tallow and expanded graphite; The expanded graphite is the expanded graphite according to claim 6.

8. The composite phase change material according to claim 7, characterized in that: The melting point of the paraffin wax is 100-107°C; The mass ratio of the paraffin wax to the tallow is 1-9:1-9; the mass percentage of the expanded graphite in the composite phase change material is 4.5-5.5%.

9. The composite phase change material according to claim 7, characterized in that: The melting point of the composite phase change material is 70-80° C., and the latent heat of phase change is 54.55-202.8 J / g.

10. The method for preparing the composite phase change material according to any one of claims 7 to 9, characterized in that: The following steps are involved: The composite phase change material is obtained by mixing paraffin wax, beef tallow and expanded graphite.

Citation Information

Patent Citations

  • Hot phase-change heat-insulating material for heat insulation of winter plastic shed and preparation of hot phase-change heat-insulating material

    CN106010455A

  • Expanded graphite filter material and preparation method thereof

    CN106422528A

  • Preparation method of 3D printing reduced graphene oxide filter element for treating uranium-containing wastewater

    CN112973640A

  • Flexible composite phase change material suitable for battery thermal management as well as preparation method and application of flexible composite phase change material

    CN115404046A

  • Normal temperature and normal pressure ClO2 catalyzed oxidation process of treating high concentration organic waste water

    CN1772648A

Cited By

  • Expanded graphite-based catalyst as well as preparation method and application thereof

    CN122279652A